The use of PBL (Problem Based Learning) Methodology in Dentistry Teaching (Research, Society and Development, 2022)
The new National Curriculum Guidelines (DCNs) have required a readaptation of the methodologies used in undergraduate courses. However, the implementation of innovative forms of learning is a great challenge for the entire academic community, due to the complexity in conducting its application. PBL (Problem Based Learning), in Portuguese “Problem Based Learning”, is an example of an Active Methodology that is widespread among courses in the health area. It is characterized by its focus on the student, which requires a proactive and critical attitude, capable of developing skills to integrate theory and practice, since the student observes problem situations, reflects on their possible causes, seeks consolidated information in the scientific literature, formulates hypotheses and discusses possible diagnoses and forms of intervention with the team. The purpose of this Integrative Literature Review is to provide basic information on the use of the PBL Methodology in Dentistry courses. To this end, 10 articles were carefully selected and analyzed, published in the last 10 years and which reported the use of this methodology in the training of dentists. With the results obtained, it can be inferred that the application of the PBL methodology in Dentistry courses has enabled the training of more critical professionals capable of finding solutions for the most diverse and complex clinical cases, autonomously and effectively, thus reiterating the advantages of using active teaching-learning methodologies in health courses.